FEMINIST CRITIQUE OF THE DOMINANT POLITICAL-PHILOSOPHICAL CONCEPTIONS OF JUSTICE - Vujadinović, Dragica (Pravni zapisi, 2024)
The aim of this article is to explore prevalent absence of conceptions of gender justice within mainstream political theories and to point out the crucial importance of gender justice for theories of justice and for practicing justice. The first part explains Aristotle’s theory of justice and offers the feminist critique. Plato’s theory of justice explained in Republic, with ideas about philosopher queens, is examined in the second part. The third part discusses premodern and some contemporary theories of justice that preserve patriarchal patterns of devaluating women within a private–public dichotomy, while the fourth part presents the mainstream and feminist theories of justice that overcome a dominant pattern and affirm gender justice in a converging manner. The concluding remarks sum up the crucial role of gender justice for benchmarking further philosophizing on justice.